(untitled) (Malaysian Management Journal, 2024)
Over the last decade, the Nigerian government has undertaken a wide ranging policy, institutional, and legal initiatives to enhance the country’s public service delivery. Despite these efforts, the nation has grappled with a myriad of issues that still undermine good governance and political security. These challenges include weak institutional capacity, corruption, poor leadership, inadequate public service delivery, political instability, limited resources, poor infrastructure, and a shortage of skilled human resources. This paper examines the strategies and mechanisms employed by public administrators in Nigeria to enhance good governance and political security, analyses the impact of effective public administration on political stability and security and identifies the challenges affecting the implementation of good governance principles through public administration in Nigeria. The study has adopted the New Public Management Theory proposed by Hood in 1991 and relied on secondary data. Findings from the study show that Nigerian public administration has undergone a series of reforms to enhance good governance and political security through various strategies and mechanisms such as capacity building, international cooperation, and ethical conduct. The study also reveals that corruption and lack of accountability, bureaucratic bottlenecks and insufficient capacity among others have been identified as challenges of the implementation of good governance principles in Nigeria. The paper recommends that the encouragement and promotion of transparency and accountability be given top priority; citizen participation should also be encouraged in the planning and decision-making process; empowering local governments through the allocation of adequate resources to foster political security. The paper also recommends the establishment of a proper recruitment base to promote professionalism and meritocracy in the public service.